Energy efficient & QoS-aware medium access control protocol for wireless sensor network applications - Bashir Abdu Muzakkari
In recent times, the emergence of Wireless Sensor Networks (WSNs) has received significant attention from the researchers due to its diverse applications in many domains.In WSNs, sensors are in small size with limited battery capacity, and idle listening is the biggest problem that consumes energy the most.Most of the presented solutions suffer from high energy consumption or inefficient enerygy trad-off with other QoS metrics such as higher latency and end-to-end delay which are precarious for delay-sensitive applications such as surveillance, target tracking and monitoring of critical situations.To address this issue,this research proposes an Energy Efficient and QoS-aware MAC (EEQ-MAC) protocol for WSN.EEQ-MAC follows the Service Differentiation (DiffServ) and suggests a new prioritization scheme for performing inter-node arbitration.This technique guarantes the transmission of high priority packet ahead of non-priority packets in case of channel contention so that the latency in high priority packet is minimized.Moreover, an adaptive duty cycle mechanism that adapts the node's duty cycle to the queue size and priority class of a packet is also introduced.This mechanism is capable of reducing the delay of high priority packets and supporting the time-bounded delivery of such packets.By checking the queue size and the priority class of packets in the message queue of each node, the node determines whether or not to adjust its duty cycle.In this approach, a node increases its listen period in the event of high traffic to provide less waiting time for the packets in the queue.This is done by extending the listen period.The sender node informs the receiver of the duration for which it has to stay awake at the beginning of data transmission.There are three priority classed used,that are High,Medium and Low.Provided that the queue is not empty, the scheduler systematically select high priority packets and then it proceeds with the medium and low priority packets.To ensure energy efficiency, the node's duty cycle is dynamically adjusted according to queue length and packet priority class.Simulations are performed in Network Simulator 2 (NS2) environment.The result obtained are compared with the existing protocols, which indicated that EEQ-MAC performed significantly better than the existing protocols in terms of energy efficiency , queue management ,end-to-end delay,latency, and throughput.In light of the outcomes,it can be established that this approach has the potential to improve energy efficiency and QoS provisioning in WSNs.